A dinâmica geográfica do trabalho sazonal da colheita da maçã em Vacaria/RS - Hanauer, Ana Clarice Soares (2024)
The thesis investigates the geographic dynamics of seasonal work in apple harvesting in Vacaria/RS, focusing on temporary migrant workers. The main objective is to understand how these flows of workers are spatialized and what working conditions they face. Apple production depends on a seasonal workforce that moves from various parts of Brazil, attracted by economic factors and the need for work. The study details the apple production structure, from preparation in the orchard to harvest, and how this impacts the lives of workers. The thesis also explores the historical and social relevance of Vacaria as an apple production hub in Brazil, discussing how local companies, over the decades, came to depend on temporary and migrant workers. The figure of recruiters, or "gatos", is central to this process, as they are responsible for mobilizing this workforce and ensuring that business demands are met. The study reveals often precarious working conditions, such as low wages, long working hours and socioeconomic vulnerability. Many workers face hardships in their home regions and are forced to seek opportunities in distant areas, such as Vacaria. In addition, the thesis highlights the importance of discussing labor rights issues and how the globalization of agribusiness directly affects these workers. The research uses a historical-dialectical materialist approach, focusing on the socioeconomic implications of seasonal work and proposing structural changes that can improve the living and working conditions of these workers.